2013
DOI: 10.5665/sleep.2384
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Including a Surrogate Arousal for Sleep Apnea-Hypopnea Syndrome Diagnosis by Respiratory Polygraphy

Abstract: Incorporating a surrogate arousal measure into HRP did not substantially increase its agreement with PSG when compared with the usual procedure (HRP without surrogate arousal).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…14 , 15 , 29 HRa, pulse transit time (PTT), post-event hyperventilation, and pulse-wave amplitude (PWA) drops have been used as markers of autonomic arousals in different studies. 14 , 15 , 29 , 30 Due to its accessibility in type 3 recordings, HRa has emerged as an interesting autonomic arousal marker, and its use as a surrogate has been explored already in other investigations. 13 , 15 , 31 Although a previous study from our group showed that a cut-off value of 10 bpm correlated better with RDIe, 14 to perform this proof of concept study we decided to use a cut-off value of 5 bpm based on previous literature and on the empirical impression that such a lower cut-off would help to capture more autonomic arousal events.…”
Section: Discussionmentioning
confidence: 99%
“…14 , 15 , 29 HRa, pulse transit time (PTT), post-event hyperventilation, and pulse-wave amplitude (PWA) drops have been used as markers of autonomic arousals in different studies. 14 , 15 , 29 , 30 Due to its accessibility in type 3 recordings, HRa has emerged as an interesting autonomic arousal marker, and its use as a surrogate has been explored already in other investigations. 13 , 15 , 31 Although a previous study from our group showed that a cut-off value of 10 bpm correlated better with RDIe, 14 to perform this proof of concept study we decided to use a cut-off value of 5 bpm based on previous literature and on the empirical impression that such a lower cut-off would help to capture more autonomic arousal events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, none of the above-mentioned studies have had cost analyses to determine viability in clinical practice or multicenter design to minimize inter-center variability. Moreover, all but one 19 of these studies scored the respiratory events automatically. While automatic scoring is simpler, manual scoring has greater agreement with PSG for respiratory polygraphy, 20 and also for a single-channel nasal pressure device measured simultaneously with in-laboratory PSG.…”
Section: Effectiveness Of Home Single-channel Nasal Pressure For Sleementioning
confidence: 99%
“…In one study, 312 subjects with all the different degrees of OSA severity were analyzed, and it was concluded that the addition of PWA drops to the definition of hypopnea as a surrogate for EEG arousal could provide a more comprehensive diagnosis of OSA. Similarly, another study considered hyperventilation following flow reduction as another potential surrogate for EEG arousals 21. Nevertheless, the authors of this study concluded that in severe OSA, the use of this marker as a surrogate did not present an additional value to OSA diagnosis with PSG nor PM.…”
Section: Discussionmentioning
confidence: 84%